The Role of Green Marketing and Product Quality on Competitive Advantages of Natural Dyes Sasirangan Fabric: A Study on Small and Medium Industry (SMI) Lins Gallery in Banjarmasin, Indonesia - Salsa Winna Widya Parawangsa; Anisah, Hastin Umi (HM Publisher, 2023)
Green marketing is very important in creating a positive impact on the environment and society. By promoting environmentally friendly products and services, companies can become agents of change that contribute to improving the quality of the environment and society as a whole. In addition, Green Marketing also provides an opportunity for companies to build a positive image and strengthen relationships with consumers who are increasingly concerned about environmental issues. This study aimed to determine the role of green marketing and product quality on the competitiveness of SMI Lins Gallery in Banjarmasin. This study is qualitative research. Respondents to this study were consumers who made a one-time purchase and used the product with a total sample of 100 people. The analysis technique used in this study is SEM-PLS (structural equation modeling-partial least square) through SmartPLS 3.0 software. Green marketing has a positive and significant effect on competitive advantage in Lins Gallery's natural dye sasirangan fabric products in Banjarmasin. Product quality has a positive and significant effect on competitive advantage in Lins Gallery natural dye sasirangan fabric products in Banjarmasin.